The United Nations in the Field of Education (Constitution United Nations Educational, Scientific and Cultural Organization) - Thomas John Kenevan (Universitas Bali Dwipa, 2022)
Every international community and government in countries in the world and all components are obliged to educate the life of their nation which is one of the goals of a country. Education in principle demands the application of the principles of democracy, decentralization, justice, and upholding human rights in the life of the nation and state. In relation to education, these principles will have a fundamental impact on the content, processes and management of the education system. In addition, science and technology are developing rapidly and giving rise to new demands in all aspects of life, including in the education system. This demand concerns the renewal of the education system, including curriculum renewal, namely curriculum diversification to serve diverse students and regional potential, diversification of types of education that are carried out professionally, preparation of graduate competency standards that apply nationally in countries around the world. Education in principle demands the application of the principles of democracy, decentralization, justice, and upholding human rights in the life of the nation and state. In relation to education, the importance of the principle of preparing education funding standards for each education unit is in accordance with the principles of equity and justice implementation of school-based education management and higher education autonomy as well as the implementation of education with an open and multi-meaning system. Renewal of the education system also includes eliminating discrimination between government-managed education and community-managed education, as well as the distinction between religious education and general education. In the context of the United Nations in the field of Education, which manages the Educational, Scientific and Cultural sector, namely the United Nations Educational, Scientific and Cultural Organization, abbreviated as UNESCO.